Agricultural NGO's and their participation in the soil erosion and water quality management problem, in Ontario. - McFadden, Nanette. (University of Ottawa (Canada), 1994)
The purpose of this research is to describe and analyze the present and potential role of non-governmental organizations (NGO's) in the management of agricultural soil erosion and associated water quality decline (ASEWQ), in Ontario. A series of five tasks are associated with this research purpose. These tasks include: the cataloguing of all agricultural NGO's in Ontario; the assessment of this NGO population's vertical interaction; the assessment of the NGO population's horizontal spread; analysis of NGO mobilization potential in the area of ASEWQ management; and finally the characterization of degree of NGO favourability towards, and involvement in, ASEWQ management. Research has led to the discovery of a very large and complex population of agricultural organizations in Ontario. The horizontal distribution of this population closely reflects the geographic configuration of agricultural activity in the province. The vertical distribution reveals a high degree of organizational affiliation and networking which gives the grassroots indirect access to provincial policy influence. Despite the size, complexity and general favourability of this population towards soil conservation, few NGO's have suitable potential to mobilize on the ASEWQ issue. As a result, only a few strategically placed and organized NGO's have any involvement in controlling agricultural soil erosion. In conclusion, this research offers a series of recommendations to provincial government agricultural policy makers and future research avenues. (Abstract shortened by UMI.)
Keywords: Agriculture, Agronomy.